An international cooperation model: CIHEAM-IAMZ training activities - Romagosa I.; Cerezo M. (Agricultural higher education in the 21st century : a global challenge in knowledge transfer to meet world demands for food security and sustainability, 2015)
Since its foundation in 1969, advanced training has been the essence of the activities conducted by the Mediterranean Agronomic Institute of Zaragoza (IAMZ). IAMZ fulfils its mission, as an axis of international cooperation within the scope of agriculture, food and the environment, through two complementary training programmes: degree-leading and short duration advanced postgraduate courses for professionals. They are both clear, effective instruments of international cooperation, based to a large extent on synergies established with Spanish and international institutions of excellence. We review the activities carried out at IAMZ over the last 25 years and make a critical analysis of the demand and the pros and cons of these training programmes.
International Conference : Agricultural Higher Education in the 21st Century, 2015/06/15-17, Zaragoza (Spain)